Chemotherapy-Induced Activation of Hemostasis: Effect of a Low Molecular Weight Heparin (Dalteparin Sodium) on Plasma Markers of Hemostatic Activation - Weitz, Ilene C.; Israel, Valerie K.; Waisman, James R.; Presant, Cary A.; Rochanda, Leanne; Liebman, Howard A. (Thrombosis and Haemostasis, 2002)
To evaluate the effect of standard chemotherapeutic regimens on the hemostatic profile of patients with breast and lung carcinoma; and to evaluate the effect of a single dose of a low molecular weight (LMW) heparin, dalteparin sodium, administered prior to the chemotherapy on markers of hemostatic activation.11 patients with breast cancer and 10 patients with lung cancer receiving systemic chemotherapy were studied. 10 breast cancer patients and 9 lung cancer patients completed at least 1 cycle of treatment and had all hemostatic studies. Patients had a complete hemostatic and prothrombotic profile performed at study initiation. Markers of hemostatic activation consisting of immunoassays for thrombin-antithrombin (TAT) complex and D-dimer were measured in plasma samples obtained prior to chemotherapy and at 1, 24 and 48 h after treatment. A 2500 U dose of dalteparin was given prior to the 2nd cycle of chemotherapy; 5000 U of dalteparin was given prior to the 4th treatment cycle.Chemotherapy resulted in statistically significant increases in TAT and D-dimer for the 1, 24 and 48 h plasma samples in both the breast and lung cancer patients for all cycles of chemotherapy given without LMW heparin. There were statistically significant increases in basal thrombin generation over the 4 cycles of treatment which was unrelated to active cancer. Both pretreatment doses of dalteparin effectively prevented increases in the markers of hemostatic activation. However, in the lung cancer patients, who had significantly increased basal thrombin generation, the 5000 U dose dalteparin was more effective.Chemotherapy results in significant hemostatic activation in patients with breast and lung cancer. The effect of treatment appears to be cumulative. A single dose of LMW heparin administered prior to therapy can suppress hemostatic activation.This project was funded by a grant from the Pharmacia corporation
Keywords: Cancer; chemotherapy; hemostatic activation; thrombosis